Poductivity management in an academic library: performance measurement at Bilgi Library - Orancı, Vildan (İstanbul Bilgi Üniversitesi, 2005)
This project is about how productivity management is done in academic libraries and applications of performance measurement at Istanbul Bilgi University Library. The definitions of productivity and performance measurement in service organizations are given in the first chapter. Then the definition, the mission and the goals of academic libraries are defined in second chapter. Also it was given information about Bilgi University library covering the collection, staff, the divisions and user profile. The third chapter covers the techniques of performance measurement. The aim of measurement, the methods of the measurement and the performance indicators are also mentioned in this chapter. The importance of performance indicators is also emphasized. Lastly, survey methods which are the one of the most important tools of performance measurement are discussed. In the next chapter, performance measurement of Bilgi library starts. First, the definition of performance indicators are given then it is explained how to be calculated through statistical data of Bilgi University library. The last chapter is consist of the explaining the results of the questionnaire for this project.